PENGARUH RAGAM MOTIF, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KAIN PANTANG - Pelipa, Emilia Dewiwati; Sore, Avelius Dominggus; Jebok, Diana Mainda (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
The abstinence cloth is one that Sintang is particularly well-known for. The Dayak Ensaid Panjang group is skilled in weaving abstinence cloth, which is thought to be a representation of an ongoing event. This study attempts to ascertain how different themes, costs, and promotions affect purchases of abstinence clothing in Ensaid Panjang Village simultaneously and in part. The method adopted for this study is a quantitative method. This study used an ex-post facto methodology. The participants in this study were all Ensaid Panjang Village buyers of abstinence clothing. There are 80 participants in the study's sample. Data analysis employed the necessary tests, including the autocorrelation test, the linearity test, the multicollinearity test, the heteroscedasticity test, and the normalcy test using the Kolmogorov-Smirnov test. Multiple regression analysis, the t test, and simultaneous testing are used in data analysis. According to the study's findings, buyers of abstinence cloth in Ensaid Panjang Village are influenced by a variety of themes, prices, and partial and concurrent promotions. Other factors have an impact on R square 0.427, or 42.7% and 57.3%.